2022
DOI: 10.3390/polym14194134
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanical Properties of Plant Fiber-Reinforced Geopolymers: A Review

Abstract: Both geopolymer and plant fiber (PF) meet the requirements of sustainable development. Geopolymers have the advantages of simple preparation process, conservation and environmental protection, high early strength, wide source of raw materials, and low cost. They have broad application prospects and are considered as the most potential cementitious materials to replace cement. However, due to the ceramic-like shape and brittleness of geopolymers, their flexural strength and tensile strength are poor, and they a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 118 publications
(130 reference statements)
0
4
0
Order By: Relevance
“…In engineering practice, the type and content of the fiber and the surface shape of the fiber all affect the toughness of composite materials. The toughness of the matrix is simply a reflection of the compatibility between the fiber and the matrix, the interfacial bond and the mechanical properties of the PF itself [ 125 ]. Assaedi et al [ 51 ] found that the addition of flax fiber significantly improved the flexural strength and fracture toughness of the composites and reduced the degradation of flax fiber.…”
Section: The Path To Slow Fiber Degradationmentioning
confidence: 99%
“…In engineering practice, the type and content of the fiber and the surface shape of the fiber all affect the toughness of composite materials. The toughness of the matrix is simply a reflection of the compatibility between the fiber and the matrix, the interfacial bond and the mechanical properties of the PF itself [ 125 ]. Assaedi et al [ 51 ] found that the addition of flax fiber significantly improved the flexural strength and fracture toughness of the composites and reduced the degradation of flax fiber.…”
Section: The Path To Slow Fiber Degradationmentioning
confidence: 99%
“…PFs are very prone to alkaline degradation in the cement-based material matrix, while the degradation degree of PFs in the GP matrix is much lower [ 72 ]. The composite of PFs and GPs can overcome the disadvantage of poor durability caused by fiber degradation of composite materials, and its performance is better than that of PF-reinforced cement-based composite materials in some respects [ 73 , 74 ]. GPs not only have the advantages of low cost, environmental friendliness, and relatively low energy consumption, but they also have good compressive strength, durability, and heat resistance, as well as high fire and heat resistance [ 75 ].…”
Section: Plant Fiber-reinforced Geopolymers (Pfrgs)mentioning
confidence: 99%
“…[38]. According to different types and parts of plants, NCFs commonly used for geopolymer reinforcement can be divided into bast fibers, leaf fibers, fruit fibers, seed fibers, and stem fibers [39]; their concise classification is shown in Figure 1. According to Lv et al [11], NCFs composed of cellulose, hemicellulose and lignin have unique microstructure.…”
Section: Classification and Properties Of Ncfsmentioning
confidence: 99%